Предмет: Математика, автор: Аноним

СРОЧНООО 127 127 127​

Приложения:

Ответы

Автор ответа: sangers1959
1

Пошаговое объяснение:

(\sqrt[6]{7} -\sqrt[6]{2})*(\sqrt[6]{7} +\sqrt[6]{2})*((\sqrt[3]{7}+\sqrt[3]{2} )^2-\sqrt[3]{14})=\\=((\sqrt[6]{7})^2-(\sqrt[6]{2})^2)*((\sqrt[3]{7})^2+2*\sqrt[3]{7*2} +(\sqrt[3]{2})^2-\sqrt[3]{14})=\\(\sqrt[3]{7} -\sqrt[3]{2})*((\sqrt[3]{7})^2+\sqrt[3]{14}  +(\sqrt[3]{2})^2)=(\sqrt[3]{7})^3-(\sqrt[3]{2})^3=7-2=5.

Похожие вопросы
Предмет: Алгебра, автор: 1998Anny1998
Предмет: Математика, автор: мадра